Increasing Purchase Decision Through Brand Image - Chalilia Yuri Putri; Lutfi Lutfi; Hayati Nufus (Indonesian Journal of Innovation Multidisipliner Research, 2024)
This study aims to determine the role of brand image in mediating purchase decision factors in Telkomsel prepaid consumers in the Tangerang city. The research method used is quantitative with a descriptive approach. This study collected data based on questionnaires, and literature studies. The population in this study is the people of Tangerang city aged 17-64 years and a sample of 152 respondents was taken with accidental sampling and purposive sampling. The data analysis method used is structural equation modeling (SEM) with the SmartPLS 4 statistical analysis tool. The results of this study show that Social Media Marketing has a significant effect on Purchase Decision. Social Media Marketing has a significant effect on Brand Image. Brand Image has a significant effect on Purchase decisions. Product Quality has no effect on the Purchase Decision. Product Quality moderates the negative direction of the relationship between Social Media Marketing and Purchase Decision. Brand Image mediates the relationship between Social Media Marketing and Purchase Decision.